(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article analyzes the types of metaphor in fiction and their impact on the aesthetic and semantic properties of literary texts. The main types of metaphor, metonymy, synesthesia, irony, and allegory examined, and their functions in a work of fiction and the emotional impact they have on the reader analyzed.